94 ALLOTRANSPLANTATION WITH REDUCED INTENSITY CONDITIONING THAT INCLUDES ALEMTUZUMAB LESSENS INCIDENCE OF RELAPSE AND TRANSPLANT-RELATED MORTALITY IN PATIENTS WITH HIGH-RISK MYELOID DISEASES. (1st January 2006) - Bigelow, C.; Elkins, S.; Hardy, C.; Files, J.
Abstract : Patients with high-risk myeloid disease can be transplanted with reduced-intensity conditioning regimens that maximize duration of remission while minimizing transplant-related mortality. Incidence of survival, relapse, tempo of engraftment, and incidence of grades I-II and III-IV acute GVHD were evaluated. Three conditioning regimens have been utilized: fludarabine 30 mg/m 2 3 5 d, melphalan 140 mg/m 2 3 1 d in all groups, and alemtuzumab 20 mg/d 3 5 d (Group 1), 3 3 d (Group 2), and 3 2 d (Group 3). Fifteen patients (median age 48, range 24-58 years) were in the study. Twelve patients had AML, two had CML, and one had MDS. Six patients were in CR at the time of transplant and nine had relapsed or refractory disease. Patients were consecutively assigned to Group 1 (seven patients), Group 2 (five patients), and Group 3 (three patients). Stem cell sources included BM (four patients), PBPC (10 patients), and one cord blood transplant, related (6 patients) and unrelated (9 patients). Match grade was 6/6 for 13 transplants, 5/6 for one, and 4/6 for the cord blood. GVHD prophylaxis was standard-dose cyclosporine or tacrolimus and MMF, tapering after day 60. Median follow-up was 7 months (range 1.5-30 months). There were no WBC engraftment failures and neutrophil (ANC > 500/dL) engraftment occurred at a median of 13 days (range 10-48 days). Three patients had grade I-II acute GVHD and one had chronic GVHD. One had grade III acute GVHD. Relapse occurred in three patients and they received DLI immunotherapy. Twelve patients survived to day 100 (80%). Four were alive at 1 year and four others who are still alive have not reached the 1-year mark. Four of the seven patients died with residual disease (26%) and three died with treatment-related toxicity within the first 100 days (20%). Eight of 15 patients remain in follow-up. We conclude that the application of fludarabine, melphalan, and alemtuzumab conditioning regimens has been successful in these high-risk patients, with a low incidence of acute GVHD (27%), no neutrophil engraftment failures, and a low incidence of relapsed disease (20%).